SIMILE AS A WAY TO INTRODUCE THE MAIN PROBLEMS IN ‘WHITE TEETH’ BY ZADIE SMITH: PRAGMATIC ASPECTS - Seredina, Ekaterina Viktorovna; Dekhnich, Olga Vitalievna (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
The article aims to describe simile as a figure of speech represented in the most famous novel ‘White Teeth’ by Zadie Smith. Similes have been chosen as a base for the study due to their pragmatic potential to depict reality in post-colonial Britain. The idea of the study is to prove that simile in the novel is a rather complicated semantically and syntactically phenomenon used to introduce the key problems of the international community. The material of the study was the sentences through the novel selected on the approach that they contain the indicator like or as with the following reference. The research design outlines simile as a figure of speech with a broad range of characteristics to depict problems of the multicultural community in the modern world. The pragmatic and semantic analysis are used to describe simile representation in the text. The results of the research show the roles of the simile in presenting the key problems of the novel. These findings help to enhance the theory of simile as a potential figure of speech and make it possible to perceive Zadie Smith’s style as an influential writer in the modern world.